2016
DOI: 10.1177/0890117116661154
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Effects of PTSD Remediation in Veterans Using Clinical Emotional Freedom Techniques: A Randomized Controlled Pilot Study

Abstract: Study results identify candidate gene expression correlates of successful PTSD treatment, providing guidelines for the design of further studies aimed at exploring the epigenetic effects of EFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 58 publications
1
60
0
1
Order By: Relevance
“…Performing the EFT technique while vocalising aspects of a targeted problem (the cognitive element) has been hypothesized to decrease hyperarousal in the amygdala (the stress response area of the brain) and hippocampus (the memory area) [30], alter dopamine and serotonin ratios [17], produce connective tissue transmission of piezoelectric signals [31], and increase HPA axis regulation, which among other benefits reduces stress-related cortisol secretion [32]. Recent research in a sample of veterans with PTSD indicated regulation of six genes associated with inflammation and immunity after 10 EFT sessions, with downregulation of inflammation and stress markers and upregulation of immune markers found [33]. However, despite these studies, it has not been unambiguously established how brain activation and neural mechanisms might be affected by EFT.…”
Section: Introductionmentioning
confidence: 99%
“…Performing the EFT technique while vocalising aspects of a targeted problem (the cognitive element) has been hypothesized to decrease hyperarousal in the amygdala (the stress response area of the brain) and hippocampus (the memory area) [30], alter dopamine and serotonin ratios [17], produce connective tissue transmission of piezoelectric signals [31], and increase HPA axis regulation, which among other benefits reduces stress-related cortisol secretion [32]. Recent research in a sample of veterans with PTSD indicated regulation of six genes associated with inflammation and immunity after 10 EFT sessions, with downregulation of inflammation and stress markers and upregulation of immune markers found [33]. However, despite these studies, it has not been unambiguously established how brain activation and neural mechanisms might be affected by EFT.…”
Section: Introductionmentioning
confidence: 99%
“…Waite and Holder (2003) found that tapping on parts of the body other than meridian points also elicited effects similar to those found in previous EFT studies. However, a more recent study found epigenetic changes may serve as the mechanisms by which EFT effectively reduces PTSD symptoms (Church et al, 2018). While more research is needed to extrapolate EFT's treatment effects and the mechanisms by which it alters symptoms, one cogent advantage of EFT is ease of administration.…”
Section: Dance/movement Therapy: Tactile and Non-tactile Other-adminmentioning
confidence: 99%
“…Church, Yount et al [22] looked at gene expression correlates of successful EFT treatment of PTSD with Veterans. PTSD symptoms were significantly reduced, (p < 0001) and the differential expression of six genes was noted after 10 sessions of EFT.…”
Section: Research On Eftmentioning
confidence: 99%